2011
DOI: 10.1089/zeb.2011.0688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stocking Densities on Reproductive Performance in Laboratory Zebrafish (Danio rerio)

Abstract: Despite the growing popularity of the zebrafish model system, the optimal husbandry conditions for this animal are not well defined. The aim of this study was to examine the effect of stocking density on reproductive performance in zebrafish. In this study, undertaken by eight different zebrafish facilities, clutches of at least 200 wild-type zebrafish embryos from a single pairwise mating were produced at each participating institution and subsequently reared according to ''in-house protocols'' until they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 12 publications
5
56
0
1
Order By: Relevance
“…18 Its efficacy as a sole feed seems controversial, however. One study evaluating nonenriched Artemia found that zebrafish fed a flake diet produced larger larvae than zebrafish fed Artemia.…”
Section: Feeding Affects Zebrafish Gsimentioning
confidence: 99%
See 1 more Smart Citation
“…18 Its efficacy as a sole feed seems controversial, however. One study evaluating nonenriched Artemia found that zebrafish fed a flake diet produced larger larvae than zebrafish fed Artemia.…”
Section: Feeding Affects Zebrafish Gsimentioning
confidence: 99%
“…18 In some cases, feeds and feeding regimes are implemented without a formal evaluation. 15 At the National Institutes of Child Health and Human Development (NICHD; National Institutes of Health, Bethesda, MD) Artemia is fed twice, while the Ziegler zebrafish pellet is fed once daily to adult zebrafish, although the rationale for this feeding protocol had never been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving eight major zebrafish facilities across the world, it was found that holding densities as high as 12 fish per litre after 4 months of age did not result in negative effects on clutch size, spawning success or egg viability (Castranova et al, 2011). When mating, changes in egg production, hatching rate or larval length were not observed until a density of 60 fish per litre (Goolish et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the impact of rearing density on growth and reproduction of some fish species has been recorded like Atlantic salmon Salmo salar (Hosfeld et al 2009), rainbow trout Oncorhynchus mykiss (McKenzie et al 2012), Nile tilapia Oreochromis niloticus (Azaza et al 2013) and Japanese Medaka Oryzias latipes (Rosemore and Welsh 2012). An interesting work was carried out by Castranova et al (2011) who worked on zebrafish and suggested that using densities as high as 12 fish/liter does not have a negative effect on reproductive performance. They also suggested that further study is needed to determine the maximum stocking density, effect of water quality parameter, feed type and genetic strain on growth and reproduction of zebrafish in laboratory condition, so the study was designed to investigate the effects of stocking density on growth and survival of zebrafish (Danio rerio).…”
Section: Introductionmentioning
confidence: 99%